Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

For any postive integer number $n\ge 2$, show that


My try:let $\dfrac{1}{n}=x$, then $$\left(\dfrac{1}{n}\right)^{\frac{1}{n-1}}+\left(\dfrac{1}{n}\right)^{\frac{n}{n-1}}=x^{\frac{x}{1-x}}+x^{\frac{1}{1-x}}(0<x<1)$$ maybe use Young's inequality.

But I can't,and I think this problem have more nice methods,Thank you

share|cite|improve this question

Note that, for every $n\geqslant2$, $$ \left(\dfrac{1}{n}\right)^{\frac{1}{n-1}}+\left(\dfrac{1}{n}\right)^{\frac{n}{n-1}}=\frac{n+1}{n^{n/(n-1)}}=\mathrm e^{u(n)}, $$ where, for every $x\gt1$, $$ u(x)=\log(x+1)-\frac{x}{x-1}\log x. $$ Thus, $$ u'(x)=\frac{v(x)}{(x-1)^2},\qquad v(x)=\log(x)-2\frac{x-1}{x+1}. $$ which yields $$ v'(x)=\frac1x-\frac4{(x+1)^2}=\frac{(x-1)^2}{x(x+1)^2}. $$ Now, $v(1)=0$ and $v$ is increasing hence $v\gt0$ and $u$ is increasing on $(1,+\infty)$, in particular, for every $n\geqslant2$, $$ u(2)\leqslant u(n)\lt u(+\infty). $$ Note that $u(2)=\log3-2\log2$ and that $u(x)$ is also $$ u(x)=\log\left(1+\frac1x\right)-\frac{\log x}{x-1}, $$ hence $u(+\infty)=0$. Finally, for every $n\geqslant2$, $$ \frac34=\mathrm e^{u(2)}\leqslant\left(\dfrac{1}{n}\right)^{\frac{1}{n-1}}+\left(\dfrac{1}{n}\right)^{\frac{n}{n-1}}\lt\mathrm e^{u(+\infty)}=1. $$

share|cite|improve this answer
Thank you,It's nice.and for this right,use Bernoulli inequality:w we have $$\le 1+\dfrac{1}{n-1}(\dfrac{1}{n}-1)+\dfrac{n}{n-1}(\dfrac{1}{n}-1)=1$$ – math110 Oct 20 '13 at 17:24

I think there is a much simpler way. Notice that $\left(\frac{1}{n}\right)^{\frac{1}{n-1}}+\left(\frac{1}{n}\right)^{\frac{n}{n-1}}$ can be expressed as: $$ a_n=\frac{n+1}{n}\left(\frac{1}{n}\right)^{\frac{1}{n-1}},$$ and we only need to prove that the sequence $\{a_n\}_{n\in\mathbb{N}}$ is increasing, since its limit is clearly $1$. $a_{n+1}\geq a_{n}$ is equivalent to: $$ n^{n^2} (n+2)^{n(n-1)} > (n+1)^{2n^2-n-1}, $$ or to: $$\frac{(n+1)^{(n+1)}}{(n+2)^n}>\left(\frac{(n+1)^2}{n(n+2)}\right)^{n^2},$$ Notice that in virtue of the Bernoulli inequality the LHS is greater that $\frac{n+2}{e}$, while the RHS is smaller than $e$, so for any $n\geq 6$ the inequality holds for sure, and we have to check only $n=2,3,4,5$, for which the difference between the LHS and the RHS is indeed positive by hand (or computer) computation.

share|cite|improve this answer
This proves the inequality for $n$ large enough, not for every $n\geqslant2$. – Did Oct 20 '13 at 19:04
That's true, but one can check the other cases ($n<6$) by hand. – Jack D'Aurizio Oct 21 '13 at 7:41
Then one should add an actual proof that "the other cases" are only when $n\leqslant5$. – Did Oct 21 '13 at 8:03

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.